Feasibility Study and Impact of Daylight on Illumination Control for Energy-Saving Lighting Systems - Sulee Bunjongjit; Atthapol Ngaopitakkul (My University, 2018)
The main goal of energy conservation should be reducing the consumption of energy resources. Due to energy and environmental concerns in recent years, to reduce energy consumption in a lighting system, which has been one of the prime targets of energy saving, daylighting has been investigated and has become one of the energy-efficiency techniques widely applied in buildings. This paper presents an analysis of T5 fluorescent luminaire lighting control using daylight in a building. The study is conducted in two parts; simulation of a lecture room using the daylighting function of the DIALux program is performed to estimate the effect of daylighting on a task area (workplane). Another part is an experimental setup to evaluate the performance of a lighting control unit that is installed for a T5 fluorescent luminaire with a dimmable electronic ballast. The efficiency of the lighting control in term of illumination on the task area and energy consumption are also evaluated and compared with the standard case. The simulation results show that daylighting increases illuminance on a task area, especially on the window side, so the lighting system can significantly reduce its power consumption compared with a standard case (without lighting control). The experimental result shows that upon installing the lighting control with daylighting, both the average illuminance and the energy consumption in each time period are decreased compared with in the standard case. Lighting control with daylighting tries to set the average illuminance on a task area to less than 500 lux, corresponding to the amount of daylight passing through window shutters. The obtained results are useful for the design of a T5 fluorescent luminaire with lighting control using daylighting in a building lighting system for energy efficiency and reducing energy consumption, including the average illuminance on the task area, according to a relevant standard.
Keywords: Daylighting; Daylight; Electric light; Smart lighting; Building Energy and Comfort Optimization